Computational Fluid Dynamics Evaluation of an Oil-flooded Screw Compressor - Malael, Ion; Petrescu, Valentin (Engineering, Technology & Applied Science Research, 2023)
The cost of energy is directly influenced by geopolitical, economic, and environmental factors. There is an international trend towards renewable resources, although the implementation pace and legislation in force have issues. Complete abolishment of fossil fuels is practically impossible. Evolution is only possible with the use of these fuels but with modern, efficient equipment to reduce the pollution resulting from the process of extracting, processing, and using fossil fuels. In this paper, a screw compressor with oil injection, used in oil extraction stations, is analyzed numerically. This analysis is useful in the process of modernizing and improving the efficiency of this type of compressor, which is capable of operating in extreme working regimes, highly contaminated with impurities. The numerical analysis presented certain challenges related to biphasic flow in extremely small spaces at high compression ratios. The results include the absolute pressure variation and the flow rate variation. Regarding future research, test series will be carried out to validate the numerical results on the test bench with a 1:1 scale prototype.